Looked but failed to see: the role of gender, driver types, accident history, and licence tenure in hazard perception - Mohd Mahudin, Nor Diana; Abd Hamid, Aqbal Hafiz Izuddin; Zulkifli, Asmaa’ Athirah; Zulkifly, Nurul Izzati Asyikin (Human Factors and Ergonomics Society Malaysia, 2020)
Hazard perception is a complex process and a better understanding of the salient contributing factors for its failure could improve the existing hazard perception tests, policies, and training programmes. However, extant literature has not tackled this issue sufficiently. Using the predictive hazard perception paradigm, this study compares motorcycle hazard perception scores and total hazard perception scores of 67 participants based on gender (male, female), driver types (car drivers, dual drivers), accident history (had accident, no accident), and licence tenure (one year or less, two years, three years, four years, five years or more). The results demonstrate that males (M = 5.96, SD = .98) scored higher on the overall hazard perception task than females (M = 5.23, SD = 1.12), t(65) = 2.64, p = .01, Cohen’s d = .69. In addition, the interaction effects between gender and driver types (F(1, 67) = 3.90), indicate that higher total hazard perception scores are obtained from male participants who are dual drivers. All other comparisons are not statistically significant. Possible explanations of the results are discussed and recommendations for improving the existing hazard perception tests, licensing policies, and training programmes are offered.